Determinants of Pulmonary Tuberculosis among Inmates at Mangaung Maximum Correctional Facility in Bloemfontein, South Africa. (17th March 2015) - Nyasulu, Peter; Mogoere, Serame; Umanah, Teye; Setswe, Geoffrey
Abstract : Introduction . Correctional facilities house large number of inmates who are at high risk of developing tuberculosis (TB); however factors associated with TB among inmates at Mangaung Correctional Centre have not been studied. Study Population and Methods . We undertook a case control study and reviewed a total of 1140 medical records of inmates treated for TB between 2009 and 2010. Cases were selected randomly from the medical records of inmates who were treated. Data collected were analysed using STATA version 12.0 and determinants of TB were evaluated using multiple logistic regression analyses. Factors withP < 0.05 were considered significant. Results . Prevalence of TB was 8.8% and 52% of inmates with TB were aged 31–40 years; 58% of the TB cases were HIV positive and 34% of them had CD4 cell count 350 cells/mm 3 . Factors associated with TB among inmates were HIV coinfection (OR: 4.2; 95% CI: 2.64–7.00); previous history of TB disease (OR: 3.58; 95% CI: 2.25–5.70); and smoking (OR: 2.1; 95% CI: 1.16–3.81). Conclusion . Interventions to improve TB detection such as regular screening of inmates with such factors need to be reinforced to control transmission of TB among inmates and the community.